Study on Extrusion of Polypropylene/Ultra High Molecular Weight Polyethylene Filament as Fused Filament Fabrication 3d Printer Material - zulkifli, Nurul syahidah; BIN KAMARUDIN, KHAIRU; Radin Khairul Faizi (Progress in Engineering Application and Technology, 2025)
This study focuses on optimizing the extrusion of Polypropylene (PP) and Ultra-High Molecular Weight Polyethylene (UHMWPE) composite filaments for use in fused filament fabrication (FFF) 3D printing. An 80:20 blend of PP and UHMWPE was utilized to balance mechanical strength, flexibility, and biocompatibility. The optimization process employed a full factorial design to examine the effects of extrusion temperature (170°C–190°C) and speed (10–110 mm/min) on filament quality. Optimal conditions at 170°C and 110 mm/min produced filaments with consistent diameters of 2.78 mm (±0.2 mm). Mechanical testing revealed enhanced tensile strength and stiffness in PP/UHMWPE filaments compared to pure PP, making them suitable for load-bearing applications. Microscopic analysis confirmed improved surface morphology with minimal defects. The findings demonstrate the potential of PP/UHMWPE composite filaments for high-quality, reliable 3D printing in industrial and medical applications.